APPLICATION OF THE CONCEPT OF THE LOCAL FUTURE OF THE DAYAK NGAJU COMMUNITY (HANDEP) IN HISTORY LEARNING IN SMA 4 PALANGKA RAYA - Endang Hartati (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2018)
In education, human’s character and self existence is very important to see, grow so that someone’s/student’s potential can grow and finally becomes the character. A nation will be strong if the citizens have the sense of self-existences of his nation. The sense of self-existence will be planted well if the citizens have the horizon of the history journey of his nation. The planning of the sense of selfexistence of his nation can be done in the very strategic activities which is through the history learning in the school which indeed the full of the active, innovative and fun history learning and full with the precious heritages.